MODEL EVALUASI KIRKPATRICK PADA PELATIHAN EFFECTIVE COMMUNICATION AND COLLABORATION DI BADAN TENAGA NUKLIR NASIONAL - Shinta Tresnawati Dewi Nawangwulan, - (2021)
The impact of a training is expected to provide an increase in the competence of human resources in the organization. To find out the results, impacts and benefits obtained from the training provided to employees of an organization, it is necessary to conduct an evaluation to obtain comprehensive results so that through the research the process of testing the evaluation model of the training program will be carried out. This is important considering that it is not certain that the training provided and has absorbed large funds will give effective results in accordance with the training objectives that the organization wants to achieve. The purpose of this research is to analyze the implementation pattern/model and the impact of Kirkpatrick's evaluation model on the "Effective Communication and Colaboration" training at the National Nuclear Energy Agency, as well to analyze the determinant factors that become the indicator of success of the soft competencies development program in the "Effective Communication and Colaboration" training at the National Nuclear Energy Agency. The research methodology used a quantitative method with a survey research design, carried out on 220 respondents, namely employees as training participants and 54 other employees who were supervisors who attended the "Effective Communication & Collaboration" training at the National Nuclear Energy Agency. The conclusion of the study illustrates that the Kirkpatrick Level 3 Evaluation (behavior evaluation) has an effective impact on the training participants so that it brings better behavior change than before the training. This is supported by findings in the form of an evaluation instrument that can be used by the National Nuclear Energy Agency (BATAN), especially PUSDIKLAT BATAN, which does not yet have a soft competencies training evaluation model in order to obtain information about changes in participant behavior. Keyword: Training, Evaluation Model , Kirkpatrick.